PKM PENGUATAN BRANDING DESA SEBAGAI PELOPOR DESA DIGITAL MELALUI PELATIHAN DAN PENDAMPINGAN PEMBUATAN WEBSITE DAN MEDIA SOSIAL DI DESA TAWANGSARI TERAS BOYOLALI - Budiwati, Yulia; Kamari, Kamari; Sumardjoko, Tri; Suharto, Isman; Nurkhotiah, Siti; Dewi, Danar Kristiana; Anggraini, Cicilia Clara Devi (Nindikayla Institute, 2023)
Low understanding of websites and social media at all levels of society in Tawangsari Village. So that it is necessary to optimize the branding of Tawangsari Village, Teras District, Boyolali Regency as a digital village pioneer through training and assistance in making websites and social media for all levels of society in Tawangsari Village. the results of training and mentoring in making websites and social media in the community in Tawangsari Village, it can be concluded that the people in Tawangsari Village are able to take part in training and mentoring in making websites and social media properly in accordance with the exposure of the material and direct practice that has been given. The results of this community service program increased knowledge, digital competence and the ability to create websites and social media for village and community officials in Tawangsari Village